Ensino inclusivo em tempos de isolamento social devido a covid-19: um olhar nos desafios da docência - Fritoli, Silvana Telma de Lima (2022)
Introduction: After the World Health Organization's declaration of the pandemic caused by the new Coronavirus, one of the most worrying aspects for countries was face-to-face teaching, as the school is one of the environments with the highest risk of transmission of the virus. The premise of this study is that teachers who work in special education are facing one of the biggest challenges of their profession, needing support and guidance for a more effective work. Objective: To analyze the repercussions of remote teaching for special and inclusive education, focusing on teaching activities and their challenges. Method: Descriptive, cross-sectional and quantitative study carried out in Paraná, Brazil, in the public school system, with 323 special education teachers from the final years of Elementary School, with an electronic questionnaire, via Google forms® triggered by the Regional Education Centers. through Whatsapp® groups. The instrument had the following variables: profile of respondents; the opinion of the participants regarding the challenges faced during remote teaching; about the period of adaptation and training; about the possible setback in the students' education process and its possible causes; about digital resources used during remote teaching; about emotional and physical disorders faced by teachers and teachers' views on the goals of remote teaching in practice. Data collection took place in 2021. For data analysis, descriptive statistics were used with a chi-square test with a significance level of 5%. Public opinion survey, with unidentified participants, which complied with Resolution No. 510/2016, approval by the Research Ethics Committee No. 634721.9.0000.0107 and approval by the State Department of Education, according to Resolution No. 406/2018. Results: The 323 respondents are distributed in 21 Regional Education Centers participating in the research, with 95.7% female biological sex, and 40% of the total between the age of 50 and 59 years. It was possible to verify that this period was one of many challenges for the teachers of the Specialized Educational Service, in particular: the adaptation of the routine and the use of new technologies in remote teaching, reported by 61% of the teachers; it was evident that: not all students had adequate technology for classes, as 72.1% of teachers observed this condition; that for 66.3% of the participants, there was a lack of student interest in remote classes; as well as the lack of monitoring by the parents, with 57.6% of affirmatives; the training of the Regional Education Centers was not standard for the entire state; that 69% of the teachers had some mental disorder, and 63.8% some physical disorder, increasing the consumption of medication in this period. Conclusion: In view of these findings, in order to contribute to addressing the problems and gaps that the pandemic has brought to special and inclusive education, it is essential to develop strategies for educational support in the post-pandemic period and also to face new challenges. pandemics.